Law of the sea, environmental law, and settlement of disputes: liber amicorum Judge Thomas A. Mensah - Ndiaye, Tafsir Malick; Wolfrum, Rüdiger; König, Doris (Martinus Nijhoff, 2007)
This volume covers a variety of topics in the fields of the law of the sea and the protection of the environment.
Includes bibliographical references. - Includes bibliographical references. - Essays in English and Frenc. - Festschrift Thomas A. Mensah
Includes bibliographical references
Keywords: Festschrift; Aufsatzsammlung; Internationales Umweltrecht; Seerecht; Völkerrecht